Analysis of Land Cover Changes On Rainwater Runoff In Ciapus Sub-Watershed - Alimuddin Alimuddin; Feril Hariati; Fachruddin Fachruddin; Muhamad Lutfi; Muhamad Rizki (Journal of Applied Geospatial Information, 2022)
Ciapus Sub Watershed is part of the Cisadane watershed which passes through 3 (three) sub-districts in Bogor Regency, namely Dramaga District, Ciomas District, and Tamansari District. From 2011 to 2020 housing construction in Dramaga, Ciomas and Tamansari sub-districts increased. High enough rainfall and continuous land changes will result in water infiltration not functioning properly and will cause an increase in surface runoff. Therefore, it is necessary to know how much influence changes in land cover have on the runoff discharge of rainwater in the Ciapus sub-watershed. The purpose of this study was to identify changes in land cover in the Ciapus sub-watershed and to determine the magnitude of the increase in runoff due to changes in land cover in the Ciapus sub-watershed. The results of the analysis of the Ciapus sub-watershed have 8 types of land cover, namely water bodies, primary dry land forest, secondary dry land forest, gardens, dry land agriculture, mixed dry land agriculture, rice fields and settlements. The biggest change in land cover area between 2011 and 2020 is the increase in residential area of ​​2441.59 ha. Meanwhile, dry land agriculture experienced the largest reduction in area of ​​1288.68 ha. Based on the calculation of runoff discharge using the rational method, the amount of discharge that occurred in 2011 was 153.31 mm/second while in 2020 it was 214.99 mm/second